Does The Use of Mobile Phones by Farmers Have an Impact on Agricultural Productivity in East Java? - Siti Munawaroh (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
This study examines the use of mobile phones on agricultural productivity in East Java Province and its comparison with peer provinces. This study uses a Propensity Score Matching (PSM) approach with a probit model to analyze the impact of using mobile phones for agricultural business activities on the amount of rice output in the form of rice. The data used in this study is IFLS wave 5 2014. The estimation results show that, in general, age, education, marital status, the natural logarithm of income, the number of paddy fields, and location affect the probability of using mobile phones for agricultural purposes. On the other hand, this study also found results that the probability of using a cell phone by individuals in East Java Province is influenced by their level of education. Individual education level in East Java Province positively relates to mobile phone use. It means that the level of education can increase the probability of using mobile phones for agricultural business purposes. Furthermore, the results of the impact of mobile phone use on the amount of rice output found that, on average, individuals who use mobile phones for farming purposes in East Java will get a higher amount of rice output by 841.3 kg compared to individuals who do not use mobile phones for business agriculture.